Socio-demographic Determinants of Indonesian Mothers’ Psychological Distress during COVID-19 Pandemic - Qadariah, Laila; Abidin, Fitri Ariyanti; Lubis, Fitri Yustikasari; Anindhita, Vidya (Makara Human Behavior Studies in Asia, 2020)
The Indonesian government imposed a large-scale social restriction policy to prevent the spread of COVID-19. This policy affected the community, including mothers, and may have caused psychological strain on them. This study aimed to (i) establish a dataset on the psychological distress reported by mothers in Indonesia and (ii) identify demographic factors and pandemic-related characteristics that determine psychological distress. An online survey was administered from April 20 to April 25, 2020, and 1534 surveys were submitted. Bivariate and multivariate regression models were constructed to examine the associations between sociodemographic variables, depression, anxiety, and stress. The results demonstrated that the level of the psychological distress domain scores was relatively low; additionally, stress was reported the most, followed by anxiety and depression. The number of children and being informed of a neighbor who tested positive were correlated with depression symptoms. The mother's age and being notified of a neighbor who tested positive correlated with anxiety symptoms. The length of the marriage and being notified of a neighbor who tested positive correlated with stress symptoms. These data help identify persons at greater risk of suffering from psychological distress and provide a baseline for further research and interventions targeting the mothers' psychological distress.